A guest at the feast : essays - Tóibín, Colm, 1955- (Scribner, 2023)
"From one of the most engaging and brilliant writers of our time comes a collection of essays about growing up in Ireland during radical change; about cancer, priests, popes, homosexuality, and literature"--